Crawford Building fire in the 100 block of West Fourth Street, 1957. - Jones, Frank (Forsyth County Public Library, 1957)
TCS 4-18-57 p.2.
Crawford Building fire in the 100 block of West Fourth Street, 1957. Patterson's Drug Store is at right.
Keywords: Digital Forsyth; Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources